2006
DOI: 10.1007/s10722-005-3877-x
|View full text |Cite
|
Sign up to set email alerts
|

Nature of taro (Colocasia esculenta (L.) Schott) genetic diversity prevalent in a Pacific Ocean island, Vanua Lava, Vanuatu

Abstract: Taro (Colocasia esculenta (L.) Schott), cultivated in Veˆtuboso, a village of northern Vanuatu, Melanesia, was surveyed to: (1) assess the extent of morphological and molecular variation being maintained by growers at the village level and, (2) compare this diversity with the diversity found in the crops in Vanuatu. Ethnobotanical data were combined with AFLP analysis to elucidate possible sources of variation. Folk assessment of variation is based on: (a) morphological characteristics (11 characters), (b) nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
(15 reference statements)
2
46
0
Order By: Relevance
“…Various studies have reported the widespread occurrence and use by farmers of plants issued from true seed in different New Guinea highland farming systems (Bulmer, 1965;Yen, 1974;Schneider, 1995). Cultivation practices favour the appearance and subsequent adoption of such variants, similarly to what has been described in detail and reviewed for cassava in the Neotropics (McKey et al, 2010) and for taro in Oceania (Caillon et al, 2006;Sardos et al, 2011). In the highlands, sweet potato plants are harvested over a long period of time and then the parcel is left as fallow, giving the remaining plants ample time to reach flowering and fruiting stages.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Various studies have reported the widespread occurrence and use by farmers of plants issued from true seed in different New Guinea highland farming systems (Bulmer, 1965;Yen, 1974;Schneider, 1995). Cultivation practices favour the appearance and subsequent adoption of such variants, similarly to what has been described in detail and reviewed for cassava in the Neotropics (McKey et al, 2010) and for taro in Oceania (Caillon et al, 2006;Sardos et al, 2011). In the highlands, sweet potato plants are harvested over a long period of time and then the parcel is left as fallow, giving the remaining plants ample time to reach flowering and fruiting stages.…”
Section: Discussionmentioning
confidence: 93%
“…Variants selected by farmers are then maintained and multiplied by clonal propagation. Increasing evidence shows that many clonally propagated crops exhibit a mixed reproductive system in which evolutionary dynamics result from the interaction of clonal and sexual reproduction (Elias et al, 2001;Caillon et al, 2006;Scarcelli et al, 2006;Sardos et al, 2008;Delêtre, 2010). It has been reported that New Guinea farmers traditionally adopt sweet potato plants issued from true seed, resulting from the spontaneous germination of the numerous self-sown seeds the crop produces in New Guinean farming systems (Yen, 1974;Schneider, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that genotypes identified by scientists rarely correspond to varieties as perceived by local farmers (Caillon et al, 2006;Barnaud et al, 2007). Here, the approach used to select outstanding trees, by applying farmers' preference criteria, resulted in obtaining genotypes closely related or identical to the PM variety.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 96 varieties of taro (Colocasia esculenta) in a village in Vanuatu hold high cultural heritage value for farmers, as expressed in varieties' names and histories, their exchange potential emphasized by their rarity, and the pride farmers develop when exhibiting their know-how in open water taro pondfields (Caillon and Lanouguère-Bruneau 2005). In contrast, agronomists note that very few clones of taro were introduced in the country, and they worry about the resulting narrow genetic base; most morphological diversity is due to mutations (Caillon et al 2006). A resilience indicator regarding the number of named varieties in a village will not have the same value depending on the background and interests of each actor.…”
Section: Biocultural Approaches To Indicator Developmentmentioning
confidence: 99%